Correlation between the O 2p Orbital and Redox Reaction in LiMn0.6Fe0.4PO4 Nanowires Studied by Soft X‐ray Absorption. Issue 24 (9th November 2016) - Asakura, Daisuke; Hosono, Eiji; Okubo, Masashi; Nanba, Yusuke; Zhou, Haoshen; Glans, Per‐Anders; Guo, Jinghua
Abstract: The changes in the electronic structure of LiMn0.6 Fe0.4 PO4 nanowires during discharge processes were investigated by using ex situ soft X‐ray absorption spectroscopy. The FeL ‐edge X‐ray absorption spectrum attributes the potential plateau at 3.45 V versus Li/Li + of the discharge curve to a reduction of Fe 3+ to Fe 2+ . The MnL ‐edge X‐ray absorption spectra exhibit the Mn 2+ multiplet structure throughout the discharge process, and the crystal‐field splitting was slightly enhanced upon full discharge. The configuration‐interaction full‐multiplet calculation for the X‐ray absorption spectra reveals that the charge‐transfer effect from O 2p to Mn 3d orbitals should be considerably small, unlike that from the O 2p to Fe 3d orbitals. Instead, the O K‐edge X‐ray absorption spectrum shows a clear spectral change during the discharge process, suggesting that the hybridization of O 2p orbitals with Fe 3d orbitals contributes essentially to the reduction. Abstract : Down to the wire : The changes in the electronic structure of LiMn0.6 Fe0.4 PO4 nanowires during discharge processes were investigated by using ex situ soft X‐ray absorption spectroscopy. An important role of O 2p orbital on the redox reaction is discovered and also that Mn is redox inactive. The 3.45 V plateau is mainly attributed to a reduction reaction of Fe 3+ to Fe 2+ .